The Influence of CO2 Enrichment on Net Photosynthesis of Seagrass Zostera marina in a Brackish Water Environment - Pajusalu, Liina; Martin, Georg; Põllumäe, Arno; Paalme, Tiina (Frontiers in Marine Science, 2016)
Seagrasses are distributed across the globe and their communities may play key roles in the coastal ecosystems. Seagrass meadows are expected to benefit from the increased carbon availability which might be used in photosynthesis in a future high CO2 world. The main aim of this study was to examine the effect of elevated pCO2 on the net photosynthesis of seagrass Zostera marina in a brackish water environment. The short-term mesocosm experiments were conducted in Kõiguste Bay (northern part of Gulf of Riga, the Baltic Sea) in June-July 2013 and 2014. As the levels of pCO2 naturally range from ca. 150 μatm to well above 1000 μatm under summer conditions in Kõiguste Bay we chose to operate in mesocosms with the pCO2 levels of ca. 2000, ca. 1000 and ca. 200 μatm. Additionally, in 2014 the photosynthesis of Z. marina was measured outside of the mesocosm in the natural conditions. In the shallow coastal Baltic Sea seagrass Z. marina lives in a highly variable environment due to seasonality and rapid changes in meteorological conditions. This was demonstrated by the remarkable differences in water temperatures between experimental years of ca. 8°C. Thus, the current study also investigated the effect of elevated pCO2 in combination with short-term natural fluctuations of environmental factors, i.e. temperature and PAR on the photosynthesis of Z. marina. Our results show that elevated pCO2 alone did not enhance the photosynthesis of the seagrass. The photosynthetic response of Z. marina to CO2 enrichment was affected by changes in water temperature and light availability.